Application of Data Mining to E-Commerce Recommendation Systems - P.V.R.D. Prasad Rao, Dr; Varakumari, S; B, Vineetha; Satish, V (International Journal of Engineering and Technology, 2018)
The rising power of technology has intensely improved the information storage, collection, and manipulation ability. As the information is growing very rapid along with its complexness, data analysis has become more important. The aim of this paper is to recommend products to the user which are more likely to be purchased. This paper, first describes about different techniques for recommendation and the research regarding recommendation system, then suggests a better approach for a good recommendation system and explains the results of that approach. Here, a combination of k-means clustering algorithm and apriori algorithm on transactional dataset so that a better recommendation list can be obtained.Â